2005
DOI: 10.1111/j.1742-4658.2005.04959.x
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the plasma membrane H+‐ATPase of Saccharomyces cerevisiae by glucose is mediated by dissociation of the H+‐ATPase–acetylated tubulin complex

Abstract: We recently described the interaction of Na + ⁄ K + -ATP ase with acetylated tubulin in neural [1-3] and nonneural cells [4]. Formation of such a complex inhibits ATPase activity. Conversely, dissociation of the complex leads to activation of the enzyme. The ATPaseacetylated tubulin complex behaves as a hydrophobic

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 23 publications
0
28
0
1
Order By: Relevance
“…Furthermore tubulin seems to co-migrate with the P-type ATPase. Interestingly it was recently reported that acetylated tubulin interacts with and regulates the activity of the orthologous H ϩ -ATPase in yeast plasma membranes (63), and it is conceivable that it does the same also with the P-type ATPase in D. salina. Other reports demonstrated that tubulin interacts with plasma membranes in plants and algae and functions as a nucleation site for the association of microtubules and hence controls cell expansion and morphology (34,64,65).…”
Section: A Functional Network Involved In Salinity Tolerancementioning
confidence: 99%
“…Furthermore tubulin seems to co-migrate with the P-type ATPase. Interestingly it was recently reported that acetylated tubulin interacts with and regulates the activity of the orthologous H ϩ -ATPase in yeast plasma membranes (63), and it is conceivable that it does the same also with the P-type ATPase in D. salina. Other reports demonstrated that tubulin interacts with plasma membranes in plants and algae and functions as a nucleation site for the association of microtubules and hence controls cell expansion and morphology (34,64,65).…”
Section: A Functional Network Involved In Salinity Tolerancementioning
confidence: 99%
“…All protein-lipid “islands” are also thought to be bound to cytoskeleton elements [23]. This idea has aroused particular interest due to the finding of an acetylated tubulin-Pma1 complex in glucose-starved yeast and its dissociation under glucose addition [24]. Research has shown that the acetylated tubulin-Pma1 complex is dissociated very rapidly and that the glucose-induced increase in Pma1 activity occurs after its disintegration [24].…”
Section: Introductionmentioning
confidence: 99%
“…This idea has aroused particular interest due to the finding of an acetylated tubulin-Pma1 complex in glucose-starved yeast and its dissociation under glucose addition [24]. Research has shown that the acetylated tubulin-Pma1 complex is dissociated very rapidly and that the glucose-induced increase in Pma1 activity occurs after its disintegration [24]. On the other hand, in S. cerevisiae , the formation and stability of Pma1-containing patches have been shown not to depend on the integrity of the actin and tubulin structures [25].…”
Section: Introductionmentioning
confidence: 99%
“…The process of proton extrusion is a phenomenon associated with enzyme activity which is stimulated in presence of glucose [33]. The inhibition of this protein causes the intracellular acidification which may result in cell death.…”
Section: Resultsmentioning
confidence: 99%